Microbial biodiversity and their antimicrobial properties in the caves of the Mulu National Park World Heritage Site, Sarawak, Malaysia - Rao, Rajani Balkrishna (Curtin University, 2024)
This thesis topic provides a comprehensive overview of the microbial diversity inside Deer- and Lagang Cave (Gunung Mulu World Heritage National Park, Sarawak, Malaysia), including those of medical relevance. The study highlights the importance of the numerous other caves in the park for their potential to harbour unique microbial communities capable of producing novel antimicrobial compounds that are also effective against drug-resistant hospital strains, thereby increasing awareness of the need to conserve these unique habitats.